ANALISA MATURITY LEVEL PENCAPAIAN OPTIMASI LAYANAN TI PERGURUAN TINGGI - Friden Elefri Neno; Kusrini Kusrini; Henderi Henderi (Universitas Raharja, 2019)
Information technology (IT) is a very important requirement for all activity activities because it is believed to increase the effectiveness and efficiency of the work process. To achieve this, it is necessary to optimize the IT servants' good and correct so that the existence of IT can support the success of work in private agencies. government and education in achieving its goals. Therefore Stella Maris SimStimikom wants to know the success of the existence of information technology that supports the process of optimization of service to all academics in a university which is an unavoidable demand, the existence of a college academic information system that serves to serve the academic process of students and lecturers is a must. Measurements of the purpose of information systems is to contribute to information technology on business performance at Stella Maris Sumba Stimicom College to measure the extent of alignment between business processes, it is necessary to need an information system audit that requires a standard, then the standard used is COBIT 4.1 with the final result obtained at the maturity level value of the IT service level is at 2.51 with the description Repeatable but intuitive